2015
DOI: 10.1159/000437435
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Medicine: Review and Perspectives of Promising Baseline EEG Biomarkers in Major Depressive Disorder and Attention Deficit Hyperactivity Disorder

Abstract: Personalized medicine in psychiatry is in need of biomarkers that resemble central nervous system function at the level of neuronal activity. Electroencephalography (EEG) during sleep or resting-state conditions and event-related potentials (ERPs) have not only been used to discriminate patients from healthy subjects, but also for the prediction of treatment outcome in various psychiatric diseases, yielding information about tailored therapy approaches for an individual. This review focuses on baseline EEG mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
73
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 150 publications
(188 reference statements)
2
73
1
3
Order By: Relevance
“…In line with that, other research groups found no differences in absolute or relative theta power38 or a decreased theta power in responders to antidepressants3940. Owing to the fact that another study found decreased theta activity to be associated with non-response41, the heterogeneity in results was recently explained with the origins of the measured theta activities14: the reduced widespread frontal activity within the responders3839 was ‘considered most likely’ as a sign of reduced drowsiness which may not be the case in the study investigating frontal midline theta activity41. For theta activity specifically assessed within the anterior cingulate cortex, results are again contradictory with both decreased and increased activity to be favourable for treatment outcome111213.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In line with that, other research groups found no differences in absolute or relative theta power38 or a decreased theta power in responders to antidepressants3940. Owing to the fact that another study found decreased theta activity to be associated with non-response41, the heterogeneity in results was recently explained with the origins of the measured theta activities14: the reduced widespread frontal activity within the responders3839 was ‘considered most likely’ as a sign of reduced drowsiness which may not be the case in the study investigating frontal midline theta activity41. For theta activity specifically assessed within the anterior cingulate cortex, results are again contradictory with both decreased and increased activity to be favourable for treatment outcome111213.…”
Section: Discussionmentioning
confidence: 65%
“…Different electroencephalographic (EEG) measures have been introduced as potential biomarkers for antidepressant treatment response, such as frequency band power, alpha hemispheric asymmetry, antidepressant treatment response (ATR) index, theta cordance and event-related potentials111213141516. More recently, the assessment of arousal regulation has become a scope of research on antidepressant treatment response171819 and has been defined as a basic and trans-diagnostically relevant neurobiological dimension within the Research Domain Criteria project (RDoC)20.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the results from several studies on coherence analysis in MDD remain controversial (1027), and no study has been conducted on coherence analysis in IGD. In the present study, inter-hemispheric coherence value for the alpha band between right and left frontal regions was significantly lower in the MDD+IGD group than the MDD-only group.…”
Section: Discussionmentioning
confidence: 99%
“…Stratifying patients based on such biomarkers can potentially reduce the well-known heterogeneity in imaging studies in psychiatry and result in new insights. This burgeoning field is reviewed by Olbrich et al [13], with a focus on personalized medicine in depression and ADHD, including recent insights from the large multicentre international study to predict optimized treatment in depression (iSPOT-D), which includes 1,008 depressed patients randomized to three different antidepressants.…”
mentioning
confidence: 99%